Dynamic Loading Vulnerability Assessment of Multi-storey Buildings: Case Study of Sri Lanka Telecom Head Office Building - Sathiparan, N.; Sooriyaarachchi, H.P.; Wanniarachchi, K.S. (My University, 2013)
The paper presents a numerical study of the assessment of the Sri Lanka Telecom Head Office Building at Lotus Road, Colombo 01, affected by blasting activates. The assessment of the building under dynamic loading has been done using the finite element modeling technique (SAP2000), to find out if any deficiency of the dynamic performance of the building. Dynamic analysis show that this building performance for lateral drift, vibration and stresses developed in columns are within allowable limits, even for the intensity of the ground motion equal to MMI 5, and acceptance criteria for vibration are more critical for this building.
Keywords: Structural Assessment; dynamic Analysis